Propriedades antimicrobianas, físico-mecânicas e de liberação de fluoreto do cimento de ionômero de vidro associado ao hexametafosfato de sódio microparticulado e nanoparticulado - Hosida, Thayse Yumi [UNESP] (2015)
The aim of this study was to evaluate antimicrobial, physico-mechanical and fluoride release properties of the glass ionomer cement (GIC) associated with HMP microparticle and nanoparticle. Initially, solutions of HMP were obtained at concentrations of 1, 3, 6, 9 and 12 %, and the antibacterial activity was evaluated against Streptococcus mutans, Lactobacillus acidophilus and Actinomyces israelli by agar diffusion test. The same methodology was used to determine the antimicrobial activity of GIC associated with HMP at concentrations of 6, 9 and 12 % microparticle or nanoparticle. The release of F and HMP were determined in demineralization and remineralization solutions. Furthermore, the resistance to diametral tensile and compression, surface hardness and the degree of conversion of monomers were measured. Parametric and non-parametric tests were performed, after checking homocedasticity data (p < 0.05). The solutions of 6, 9 and 12 % of HMP showed better antimicrobial activity against all bacteria tested, and these concentrations incorporated into the CIV. All concentrations of HMP incorporated into the GIC had antimicrobial activity for all bacteria. There was a dose-response relationship between concentration of HMP in the GIC and antimicrobial activity. Regarding the release of F and HMP, higher values occurred on the first day in all groups and the highest levels of release occurred in groups containing 9 and 12 % of HMP nanoparticle. However the incorporation of HMP in the GIC reduced values of physical and mechanical tests when compared to the GIC, showing a dose-response relationship. It was concluded that the incorporation of HMP in GIC improves antimicrobial activity and increase the release of fluoride, but reduces its physical and mechanical properties. The reduction of particulate HMP led to better antimicrobial and fluoride release results